Recent Developments in Anti-dotes Against Anthrax - Dhasmana, Neha; K. Singh, Lalit; Bhaduri, Asani; Misra, Richa; Singh, Yogendra (Recent Patents on Anti-Infective Drug Discovery, 2014)
The etiologic agent of disease anthrax, Bacillus anthracis, causes recurrent outbreaks among the livestock and intermittent infections in humans across the world. Controlling animal infections by vaccination can minimize the incidence of disease in humans. Prevention of anthrax in occupationally exposed personnel is achieved through vaccination with either live spores or precipitates of culture supernatants from attenuated strains of B. anthracis. However, anthrax vaccination of the large human population is impractical as well as inappropriate. Broad-range antibiotics like amoxicillin, ciprofloxacin, clindamycin, streptomycin, and penicillin G are recommended for the treatment of human anthrax infections, but the threat of antibiotic resistant strains always remains. Moreover, in the absence of any specific symptom (s) during early infection, the diagnosis of anthrax is delayed causing elevated levels of anthrax toxin component which could be fatal. For these reasons, there is a need to develop new antimicrobial agents against virulent B. anthracis to effectively combat this fatal pathogen. Over the last two decades, extensive studies have been carried out to develop specific inhibitors against virulence factors of B. anthracis such as capsule, protective antigen, lethal factor and edema factor. Research has also been focused in developing inhibitors of anthrax toxin receptors (including the use of receptor decoys) and host furin endoproteases which are required for activation of toxin. This review highlights the recent progress made in developing the diverse countermeasures for anthrax infections targeting B. anthracis virulence factors and their counterparts in host.
Keywords: spore